2012
DOI: 10.1111/j.1601-5037.2012.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of manual toothbrushes following a brushing exercise: a systematic review

Abstract: The efficacy in plaque removal following a brushing exercise is a reduction from baseline plaque scores of 42% on average, with a variation of 30-53% dependent on the plaque index used. The available evidence indicates that bristle tuft arrangement (flat trim, multilevel, angled) and brushing duration are factors that contribute to the variation in observed efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
173
2
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(203 citation statements)
references
References 44 publications
10
173
2
12
Order By: Relevance
“…A recent systematic review on the efficacy of manual toothbrushes demonstrated that plaque removal was clearly better after brushing for 2 min (41 % mean plaque reduction) than for 1 min (27 % mean plaque reduction) [40]. In the present study, the mean brushing duration was 156 s, and only 14 % of subjects brushed for less than 90 s, which was considerably longer than previously published: between 31 and 67 s [14,15,19,20,41], 96 [24] and 117 s (6-12-year-olds) [23].…”
Section: Discussionmentioning
confidence: 96%
“…A recent systematic review on the efficacy of manual toothbrushes demonstrated that plaque removal was clearly better after brushing for 2 min (41 % mean plaque reduction) than for 1 min (27 % mean plaque reduction) [40]. In the present study, the mean brushing duration was 156 s, and only 14 % of subjects brushed for less than 90 s, which was considerably longer than previously published: between 31 and 67 s [14,15,19,20,41], 96 [24] and 117 s (6-12-year-olds) [23].…”
Section: Discussionmentioning
confidence: 96%
“…According to a study by Löe and Kleinmann, 18 three main factors are associated with the efficacy of plaque removal by tooth brushing: 1) the design of the brush, 2) the skill of the individual using the brush, and 3) the frequency and duration of use. A systematic review by Slot et al 19 evaluated the efficacy of a brushing exercise on plaque scores. A meta-analysis of 59 studies revealed that a single brushing exercise reduced plaque scores from 30% to 53% of baseline.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…However, a number of factors can hinder optimal tooth brushing including individuals' incompetency in toothbrushing habit, degree of periodontal tissue change due to gingivitis or periodontitis, bristle arrangement or flexibility and type of toothbrush or toothpaste 23) . Furthermore, a recent systematic review assessing the efficacy in dental plaque removal showed that following a single brushing exercise, the plaque reduction is only 42% on average 24) . Considering that such remnant plaque on tooth surfaces can cause gingivitis, the use of adjunctive cleaning agents such as mouthrinses should be integrated into oral hygiene care routine.…”
Section: Discussionmentioning
confidence: 99%